How to build resilience to conflict: The role of food security - Breisinger, Clemens; Ecker, Olivier; Maystadt, Jean-François; Trinh Tan, Jean-François; Al-Riffai, Perrihan; Bouzar, Khalida; Sma, Abdelkarim; Abdelgadir, Mohamed (International Food Policy Research Institute, 2014)
This Food Policy Report explains why there is a need to place even higher priority on food security-related policies and programs in conflict-prone countries, and offers insights for policymakers regarding how to do so. To understand the relationship between conflict and food security, this report builds a new conceptual framework of food security and applies it to four case studies on Egypt, Somalia, Sudan, and Yemen. It argues that food security-related policies and programs build resilience to conflict insofar as they are expected not only to help countries and people cope with and recover from conflict but also to contribute to preventing conflicts and support economic development more broadly: by helping countries and people become even better off.